2003
DOI: 10.1081/jdi-120021159
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Pentoxifylline with Angiotensin Converting Enzyme Inhibitors Produces an Additional Reduction in Microalbuminuria in Hypertensive Type 2 Diabetic Patients

Abstract: Our findings suggest that the combination of pentoxifylline with an angiotensin converting enzyme inhibitor in hypertensive type 2 diabetic patients with persistent microalbuminuria causes a significant reduction in urinary albumin excretion and this effect seems independent from blood pressure and glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 11 publications
(12 reference statements)
1
33
0
Order By: Relevance
“…It had been shown that pentoxifylline reduces urinary protein excretion in diabetic subjects, both with normal renal function [166,167] and renal insufficiency [155]. Furthermore, prospective trials have demonstrated that the addition of pentoxifylline to blockers of the RAS (ACEIs [168] and ARBs) [169] is associated with a significant reduction in urinary albumin excretion. Finally, in a previous study in patients with proteinuric primary glomerular diseases, in addition to the previously described effects on TNF-α, pentoxifylline significantly reduced urinary protein excretion, which was closely associated with a decrease in urinary MCP-1 excretion [170].…”
Section: Tnf-αmentioning
confidence: 97%
“…It had been shown that pentoxifylline reduces urinary protein excretion in diabetic subjects, both with normal renal function [166,167] and renal insufficiency [155]. Furthermore, prospective trials have demonstrated that the addition of pentoxifylline to blockers of the RAS (ACEIs [168] and ARBs) [169] is associated with a significant reduction in urinary albumin excretion. Finally, in a previous study in patients with proteinuric primary glomerular diseases, in addition to the previously described effects on TNF-α, pentoxifylline significantly reduced urinary protein excretion, which was closely associated with a decrease in urinary MCP-1 excretion [170].…”
Section: Tnf-αmentioning
confidence: 97%
“…Moreover, clinical trials have shown that pentoxifylline reduces urinary protein excretion in diabetic patients with normal renal function as well as in those with renal insufficiency [128,134,135] . In addition, combination of pentoxifylline and renin-angiotensin system blockers shows an additive antiproteinuric effect [136,137] .…”
Section: Il-18 Is An Inflammatory Cytokine Recently Involvedmentioning
confidence: 99%
“…Interestingly, a recent work demonstrated that PTF (400 mg three times a day) resulted in an equivalent antiproteinuric effect to captopril (25 mg three times a day) [28]. Finally, combination of PTF with blockers of the renin-angiotensin system [29,30] is associated with significant reduction in urinary albumin excretion. Importantly, diabetic patients under long-term treatment with angiotensin II receptor blockers who present residual albuminuria, an independent predictor of the rate of decline in the glomerular filtration rate, may obtain a beneficial additive antiproteinuric effect after administration of PTF, which is associated with a reduction of urinary TNF-α excretion [30].…”
Section: Treatment Of Dn: New Perspectivesmentioning
confidence: 94%